Endlessness of Statelessness - Sanubari, Robindra Akhmad; Antikowati, Antikowati; Yunita, Fenny Tria (Universitas Jember, 2024)
Citizenship Status is a human right and is crucial for people to receive protection from the state. Human rights are a fundamental element of the state, and citizenship status creates a mutual relationship between citizens and their country. Everyone must have citizenship because the relationship between the state and the citizen grants legal certainty. This study aims to determine and analyze the legal protection of stateless persons living and settling in Indonesia. Additionally, this article examines what legal remedies are available to stateless persons to obtain citizenship status in Indonesia. This research is normative research based on societal norms. The research type is based on the absence of regulation concerning non-stateless persons in Indonesia in Law No. 12 of 2006 concerning Citizenship and Government and Regulation No. 2 of 2007 concerning the Procedure to Obtain, Lose, Cancellate, and Retrieve Indonesian Citizenship. Based on the research results, it can be concluded that stateless persons in Indonesia (pid) are protected by the principles of anti-apatride and the concept of maximum protection. Consequently, the government has the discretion to ensure that former citizens and their descendants who lost Indonesian citizenship can recover their status as Indonesian citizens. Keywords: Citizenship, Human Rights, Stateless Persons, Statelessness.